Successful treatment of CMV, EBV, and adenovirus tissue infection following HLA‐mismatched allogeneic stem cell transplant using infusion of third‐party T cells from multiple donors in addition to antivirals, rituximab, and surgery. Issue 2 (6th December 2020) - Di Ciaccio, Pietro R.; Avdic, Selmir; Sutrave, Gaurav; Clancy, Leighton; Withers, Barbara; Blyth, Emily; McLeod, Duncan; Gottlieb, David J.
Abstract: Viral infections, principally cytomegalovirus, Epstein Barr virus (EBV) and adenovirus, are a leading cause of morbidity and mortality after allogeneic stem cell transplantation. The use of systemic antivirals is limited by limited efficacy and organ toxicities. Inability to clear infection is exacerbated by transplant‐related immunosuppression and prophylaxis or treatment of acute graft versus host disease. We report the first patient to clear three serious viral infections after stem cell transplant using third‐party donor partially human leukocyte antigen (HLA) matched virus‐specific cytotoxic T cells. The patient, a 53 year old female with transplanted for relapsed leukemia, with severe graft versus host disease received five T cell infusions from three separate donors that ultimately cleared serious systemic infections with cytomegalovirus and adenovirus, and an EBV‐driven lymphoma. Systemic antivirals had resulted in failed clinical responses. Use of repeated infusions of partially HLA matched virus‐specific T cells from banks containing cryopreserved cells should be strongly considered in transplant recipients with single or multiple refractory viral infections.